Nitric oxide-releasing or generating surfaces for blood-contacting medical devices - Zang, Yanyi, author; Reynolds, Melissa, advisor; Kipper, Matt, committee member; Li, Yan Vivian, committee member; Zabel, Mark, committee member (Colorado State University. Libraries, 2020)
Medical device-induced thrombosis is a major complication that impairs the expected performance of blood-contacting medical devices. Traditional anticoagulation therapies are used to reduce thrombus formation; however, systemic anticoagulants such as heparin increase the risk of thrombocytopenia or even bleeding, which are detrimental to patients who already have injuries. To address these issues, surface modification has been widely studied to improve the performance of blood-contacting medical devices, ranging from biopassive surfaces to biomimetic surfaces. To date, such modifications are not sufficient to prevent blood clotting alone. Supplementary anticoagulation remains necessary to maintain clot-free surfaces. Nitric oxide (NO) is a well-known signaling molecule that has antiplatelet properties. Our approach is to use surfaces that can either release NO via NO donors or promote NO production via an NO catalyst. In this work, a NO-releasing polyelectrolyte multilayer coating effectively reduces platelet adhesion, platelet activation and delay blood clotting on titania nanotube array surfaces. In addition, NO-releasing polymeric surfaces mediate blood serum protein deposition in a manner that prevents platelet adhesion and platelet activation. However, the NO donors used in these two coatings are photo- and thermo- sensitive, and the NO release is limited by the amount of NO donor added to the coating. To overcome these shortcomings, a copper-based metal organic framework (MOF) was used to infinitely promote NO production from NO donors in the blood. The copper-based MOF polymer coating was successfully applied to the surfaces of extracorporeal life support catheters and circulation tubing via custom coating systems. These copper-based MOF-coating also exhibited inherent antibacterial properties under both static and dynamic flow conditions.
Keywords: ECLS; metal-organic framework; coating; nitric oxide; medical devices